Thymic epithelial cells require p53 to support their long-term function in thymopoiesis in mice - Rodrigues, PM (2017)
Thymic epithelial cells (TECs) provide crucial microenvironments for T-cell development and tolerance induction. As the regular function of the thymus declines with age, it is of fundamental and clinical relevance to decipher new determinants that control TEC homeostasis in vivo. Beyond its recognized tumor suppressive function, p53 controls several immunoregulatory pathways. To study the cell-autonomous role of p53 in thymic epithelium functioning, we developed and analyzed mice with conditional inactivation of Trp53 in TECs (p53cKO). We report that loss of p53 primarily disrupts the integrity of medullary TEC(mTEC) niche, a defect that spreads to the adult cortical TEC compartment. Mechanistically, we found that p53 controls specific and broad programs of mTEC differentiation. Apart from restraining the expression and responsiveness of the receptor activator of NF-kappa B (RANK), which is central for mTEC differentiation, deficiency of p53 in TECs altered multiple functional modules of the mTEC transcriptome, including tissue-restricted antigen expression. As a result, p53cKO mice presented premature defects in mTEC-dependent regulatory T-cell differentiation and thymocyte maturation, which progressed to a failure in regular and regenerative thymopoiesis and peripheral T-cell homeostasis in the adulthood. Lastly, peripheral signs of altered immunological tolerance unfold in mutant mice and in immunodeficient mice that received p53cKO-derived thymocytes. Our findings position p53 as a novel molecular determinant of thymic epithelium function throughout life.